Social Media, Public Health, and Community Mitigation of COVID-19: Challenges, Risks, and Benefits - Corey H Basch; Charles E Basch; Grace C Hillyer; Zoe C Meleo-Erwin (JMIR Publications, 2022)
Shortly after the first case reports in 2019, COVID-19 was declared a pandemic. Early messages from trusted experts, which later proved to be inadequate or incorrect, highlight the need for continual adjustment of messages to the public as scientific knowledge evolves. During this time, social media exploded with greatly sought-after information, some of which was misinformation based on incomplete or incorrect facts or disinformation purposefully spread to advance a specific agenda. Because of the nature of social media, information, whether accurate or not at the time posted, lives on and remains accessible to the public even when its usefulness has been discredited. While the impact of mis/disinformation on COVID-19 risk-reducing behaviors is debatable, it is clear that social media has played a significant role in both extending the reach of COVID-19-related falsehoods and promoting evidence-based content. Over the last decade, social media has become a dominant source of information that consumers turn to for health information. A great deal of misinformation and disinformation has reached large numbers of social media users, which points to a need for the agencies of the US Public Health Service to create communications to convey accurate and current information and appeals that will actually be viewed. This viewpoint highlights the challenges, risks, and potential benefits that social media present in mitigating the COVID-19 pandemic.